Develop Tourism Destination Attributes for Marlina Group to Enhance Customer Intention to Visit - Utomo, Farhan Aditya; Windasari, Nila Armelia (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to develop tourism destination attributes for Marlina Group in Lemahsugih, Majalengka, to enhance customer intention to visit. The research applies a mixed-method approach combining qualitative exploration and quantitative validation. Qualitative data were collected through in-depth interviews with key stakeholders, including tourism practitioners, government representatives, and the Marlina Group management, to identify gaps and opportunities across six tourism destination attributes: Accessibility, Attraction, Activities, Available Packages, Ancillary Services, and Amenities (6A). Quantitative data were obtained from 376 respondents through structured questionnaires, and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test the relationships between these attributes and intention to visit. The findings reveal that Accessibility, Attractions, and Activities are the most influential factors in shaping tourist intention to visit, while Ancillary Services, Amenities and Available Packages play supporting roles than being primary drivers. The study contributes both theoretically, by extending tourism destination attribute frameworks in the context of rural tourism, and practically, by providing Marlina Group with a structured strategy to transform Lemahsugih from a supporting agro-tourism area into a competitive rural tourism destination